Study on Ameliorative Effect of Febuxostat on Gout Induced Model in Broiler Chicks - Patel, M.K.; Dave, C.J.; Rathod, R.C.; Joshi , B.P.; Ghodasara, D.J. (Indian Journal of Veterinary Sciences and Biotechnology, 2017)
This work was conducted on six groups of day-old Cobb-400 broiler chicks to study the ameliorative effect of febuxostat on gout induced model. Clinical signs were noticed in birds of diclofenac control group II and low dose febuxostat treated group IV. During the study, 27.77% and 22.22% mortality were observed in diclofenac control group II and low dose febuxostat treated group IV, respectively. Febuxostat control group III and febuxostat (medium and high dose) treated groups V and VI had no mortality. Reduction in body weight gain and feed intake was observed in diclofenac control group II as compared to without treatment control group I at the end of every week during the experimental period of 21 days. Reduction in body weight gain and feed intake was observed in low dose febuxostat treated group IV as compared to control group at the end of 1st week. The average FCR was higher in diclofenac control group II (2.54) and low dose febuxostat treated group IV (2.14) as compared to control group (2.00). Kidney: body weight ratio was significantly high in diclofenac control group II as compared to control group at the end of experiment. Gross and microscopic lesions of visceral gout were mainly observed in chicks that died during the experiment from diclofenac control group II and low dose febuxostat treated group IV. The overall lesions showed that diclofenac was nephrotoxic and hepatotoxic in nature. Febuxostat at lower than the therapeutic dose did not prevent nephrotoxicity and hepatotoxicity caused by diclofenac leading to visceral gout. Febuxostat control III and febuxostat (medium and high dose) treated groups V and VI did not reveal any pathomorphological changes. Judicious use of febuxostat is safe in poultry birds between the limit of 4 mg/kg and 6 mg/kg.
Keywords: Ameliorative effect; Febuxostat; Diclofenac; Gout; Broiler chicks